2022
DOI: 10.3389/fpsyt.2022.864481
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Stimulation of Prefrontal Cortex Improves Lipopolysaccharide-Induced Depressive-Like Behaviors in Mice

Abstract: Increasing evidence indicates that inflammatory responses may influence brain neurochemical pathways, inducing depressive-like behaviors. Ultrasound stimulation (US) is a promising non-invasive treatment for neuropsychiatric diseases. We investigated whether US can suppress inflammation and improve depressive-like behaviors. Mice were intraperitoneally injected with lipopolysaccharide to induce depressive-like behaviors. Ultrasound wave was delivered into the prefrontal cortex (PFC) for 30 min. Depressive- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 72 publications
0
15
1
Order By: Relevance
“…The EPM test is another specific experimental paradigm for examining the state of anxiety in mice ( 30 , 31 ). The EPM is composed of a pair of opposite open arms (35 cm × 5 cm) and a pair of opposite closed arms (35 cm × 5 cm × 15 cm) and a central area, which cross each other in a cross shape.…”
Section: Methodsmentioning
confidence: 99%
“…The EPM test is another specific experimental paradigm for examining the state of anxiety in mice ( 30 , 31 ). The EPM is composed of a pair of opposite open arms (35 cm × 5 cm) and a pair of opposite closed arms (35 cm × 5 cm × 15 cm) and a central area, which cross each other in a cross shape.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasound pulse signals were generated by a signal generator (DG4162, RIGOL, Beijing, China). Pulse signals were amplified through a power amplifier (LZY‐22+, MiniCircuits, Brooklyn, NY), and then transmitted to an ultrasound transducer (diameter = 20 mm, focal distance = 19 mm) (1905055, ndtXducer, Northborough, MA) with 1.0 MHz fundamental frequency 32 . The details of the focused transducer parameters shown in Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…Pulse signals were amplified through a power amplifier (LZY-22+, MiniCircuits, Brooklyn, NY), and then transmitted to an ultrasound transducer (diameter = 20 mm, focal distance = 19 mm) (1905055, ndtXducer, Northborough, MA) with 1.0 MHz fundamental frequency. 32 The details of the focused transducer parameters shown in Figure S1. The ultrasound parameters were generally carried out as described by the previous study and as shown in Figure 1B 30 : Anesthesia was induced in animals with 5% isoflurane and then maintained with 1.5 to 2% isoflurane through a face mask.…”
Section: Low-intensity Focused Ultrasoundmentioning
confidence: 99%
“…Sha-Sha Yi et al recently found that LIFUS can alleviate the behaviors of lipopolysaccharide-induced depressed mice. Moreover, the lipopolysaccharide-mediated upregulation of inflammatory cytokines was significantly reduced by LIFUS ( 95 ). As in other neurological disorders, the therapeutic effects of some drugs and other factors on depression are limited by the intrinsic properties of the BBB.…”
Section: Ultrasonic Stimulation In Central Nervous System Diseasementioning
confidence: 99%